Ultrasound-Guided Transmuscular Quadratus Lumborum Block Reduces Postoperative Pain Intensity in Patients Undergoing Total Hip Arthroplasty: A Randomized, Double-Blind, Placebo-Controlled Trial - Jian He; Lei Zhang; Wan You He; Dong Lin Li; Xue Qin Zheng; Qi Xia Liu; Han Bin Wang (Pain Research and Management)
Background and Objectives. Pain management following total hip arthroplasty (THA) has been widely investigated; however, the best effective method is yet to be determined. The aim of this prospective, placebo-controlled study was to evaluate the analgesic efficacy of ultrasound-guided QL3 block in patients undergoing THA. Methods. Eighty-eight patients undergoing THA were randomized to receive 0.33% ropivacaine (Group QLB, n = 44) or saline (Group Con, n = 44) for QL3 block. Spinal anesthesia was then performed. Pain intensity was assessed using the visual analog scale (0: no pain to 10: worst possible pain). The primary outcome was pain scores recorded at rest at 3, 6, 12, 24, 36, and 48 h and on standing and walking at 24, 36, and 48 h postoperatively. Secondary outcomes were analgesic consumption, side effects, the 10-meter walking speed on day 6, and patient satisfaction after surgery. Results. Postoperative pain intensity was significantly lower in Group QLB compared to Group Con at rest after 3, 6, 12, 24, 36, and 48 h (p<0.001) and during mobilization after 24, 36, and 48 h (p<0.001). Morphine use was significantly lower in Group QLB compared to Group Con during 0–24 h (16.0 ± 7.1 vs. 34.1 ± 7.1 mg, p<0.001) and during 24–48 h (13.0 ± 4.0 vs. 17.4 ± 4.6 mg, p<0.001) postoperatively. The 10-meter walking speed was higher in Group QLB compared to Group Con, both at comfortable (0.79 ± 0.13 vs. 0.70 ± 0.14 m/s, p=0.012) and at maximum speeds (1.18 ± 0.26 vs. 1.06 ± 0.22 m/s, p<0.001). Incidences of nausea (7.3% vs. 31%, p=0.006), vomiting (7.3% vs. 26.2%, p = 0.022), and urinary retention (9.8% vs. 28.6%, p=0.030) were lower in Group QLB than in Group Con. Conclusions. Ultrasound-guided QL3 block is an effective pain management technique after THA.